Loss-of-function Mutation in PMVK Causes Autosomal Dominant Disseminated Superficial Porokeratosis - Wang, Jiuxiang; Liu, Ying; Liu, Fei; Huang, Changzheng; Han, Shanshan; Lv, Yuexia; Liu, Chun-Jie; Zhang, Su; Qin, Yayun; Ling, Lei; Gao, Meng; Yu, Shanshan; et al. (Scientific reports, 2016)
Disseminated superficial porokeratosis (DSP) is a rare keratinization disorder of the epidermis. It is characterized by keratotic lesions with an atrophic center encircled by a prominent peripheral ridge. We investigated the genetic basis of DSP in two five-generation Chinese families with members diagnosed with DSP. By whole-exome sequencing, we sequencing identified a nonsense variation c.412C > T (p.Arg138*) in the phosphomevalonate kinase gene ( PMVK ), which encodes a cytoplasmic enzyme catalyzing the conversion of mevalonate 5-phosphate to mevalonate 5-diphosphate in the mevalonate pathway. By co-segregation and haplotype analyses as well as exclusion testing of 500 normal control subjects, we demonstrated that this genetic variant was involved in the development of DSP in both families. We obtained further evidence from studies using HaCaT cells as models that this variant disturbed subcellular localization, expression and solubility of PMVK. We also observed apparent apoptosis in and under the cornoid lamella of PMVK-deficient lesional tissues, with incomplete differentiation of keratinocytes. Our findings suggest that PMVK is a potential novel gene involved in the pathogenesis of DSP and PMVK deficiency or abnormal keratinocyte apoptosis could lead to porokeratosis.